Listening Skills in Classroom Practices and Testing Systems at the Secondary Level in Bangladesh: An Empirical Appraisal - Jamila, Marium; Rahman, Md. Munibur (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Developing language skills is a must for being proficient in any language for successful communication which is one of the most sought-after soft skills in the world today. Given the poor English proficiency of Bangladeshi students, this study investigated the status of listening skills, one of the vital primary language skills, in classroom practices and testing systems at the secondary level in Bangladesh. In this mixed methods research, twelve teachers from different secondary level schools and seventy students from two schools in Jashore district, Bangladesh were surveyed with structured questionnaires. Moreover, semi-structured interview sessions were conducted with six teachers. Simultaneously, the contents of the textbook 'English for Today' (for Classes Nine and Ten), and the Secondary School Certificate (SSC) examination question papers were also analyzed. The overall findings of this study revealed that listening skills did not have adequate attention and necessary importance in the textbook contents, classroom teaching-learning processes, and testing systems. The existing teaching-learning practices have substantially failed to impart optimum English proficiency, especially listening skills to the students. Therefore, this research recommends the incorporation of listening skills into classroom activities and testing systems proportionately.